Method for manufacturing a hairspring for a watch movement

Through the annealing, cooling, deformation and heat treatment of niobium and hafnium alloys, combined with the deposition of ductile material layers, the adhesion and biting problems of watch hairspring during drawing and rolling are solved, and high yield strength and low magnetic field sensitivity are achieved. The manufacturing process simplifies the manufacturing process and improves mechanical properties.

CN111913380BActive Publication Date: 2025-01-17NIVAROX FAR SA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202010372078.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-07
Filing Date
2020-05-06
Publication Date
2025-01-17
Estimated Expiration
2040-05-06

AI Technical Summary

Technical Problem

Existing watch and hairspring manufacturing technology is difficult to solve the adhesion and bite problems of niobium and hafnium alloys during drawing and rolling, especially the ease of rolling operation while maintaining high yield strength, easy manufacturing and low magnetic field sensitivity. There are shortcomings in terms of aspects.

Method used

Using a blank made of niobium and hafnium alloy, wires are formed by annealing, cooling, deformation and winding steps, and a layer of ductile material is deposited on the blank to facilitate molding, and finally heat treatment is performed to improve mechanical properties and reduce the thermoelastic coefficient.

Benefits of technology

The manufacturing of the hairspring with high yield strength and low elastic modulus is achieved, simplifying the drawing, wire drawing and rolling operations, ensuring the high mechanical properties and paramagnetic properties of the hairspring, while having a thermoelastic coefficient of almost 0 at normal operating temperatures.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a balance spring to be fitted to a balance wheel of a timepiece movement, comprising: - a step of manufacturing a blank made of a niobium and hafnium alloy containing 5 to 60% by weight, preferably 5 to 30% by weight, more preferably 8 to 12% by weight of hafnium, - a step of annealing and cooling said blank, - at least one step of deforming the annealed blank to form a wire, characterized in that it comprises, before the deformation step, a step of depositing on said blank a layer of a ductile material chosen from copper, nickel, copper-nickel alloys, copper-manganese alloys, gold, silver, nickel-phosphorus Ni-P and nickel-boron Ni-B to facilitate the wire forming operation. The invention further relates to a balance spring made by said manufacturing method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a hairspring to be assembled on a balance wheel of a timepiece movement. It also relates to a hairspring made of a Nb-Hf alloy using this method. Background Art

[0002] The manufacture of balance springs for watches is subject to constraints that often seem incompatible at first glance:

[0003] -High yield strength is required,

[0004] -Ease of manufacturing, especially wire drawing and rolling operations,

[0005] -Excellent fatigue strength,

[0006] - stability of performance levels over time,

[0007] - Small cross section.

[0008] The manufacture of the hairspring also focuses on temperature compensation to ensure a consistent level of chronometric performance. This requires obtaining a thermoelastic coefficient close to 0. Hairsprings with limited sensitivity to magnetic fields are also sought.

[0009] Balance springs have been developed using niobium and hafnium alloys. However, these alloys cause problems involving sticking and galling in the drawing or drawing templates (diamond or hard metal) and on the rollers (hard metal or steel), making it almost impossible to convert them into fine wires using standard methods such as for steel.

[0010] Any improvement in at least one of these points, particularly ease of manufacture, and in particular ease of wire drawing and rolling operations, therefore represents a significant advance. Summary of the invention

[0011] One object of the present invention is to propose a method for manufacturing a balance spring to be fitted to a balance of a timepiece movement which facilitates the deformation and more particularly the rolling operation.

[0012] To this end, the invention relates to a method for manufacturing a balance spring to be fitted to a balance wheel of a timepiece movement, comprising:

[0013] - a step of manufacturing a billet made of a niobium and hafnium alloy, said alloy containing:

[0014] -Niobium: up to 100% by weight

[0015] - hafnium: between 5 and 60% by weight, preferably between 5 and 30% by weight, more preferably between 8 and 12% by weight,

[0016] - one or more elements selected from Ti, Zr, Ta and W, the percentage of each element being in the range of 0 to 2 wt. %, preferably in the range of 0.2 to 1.5 wt. %,

[0017] - impurities, the total percentage of which is in the range of 0 to 0.5 wt. %. More specifically, the impurities may be trace elements selected from O, H, C, Fe, N, Ni, Si, Cu, Al, Cr, Mn, V, Sn, Mg, Mo, Pb, Co and B, each of which is present in an amount of 0 to 1,000 wt. ppm,

[0018] - a step of annealing and cooling the billet, followed by a step of deforming the annealed billet to form a wire, said annealing and deformation steps being repeated several times,

[0019] - a winding step for forming a balance spring,

[0020] - Final heat treatment step.

[0021] According to the invention, the method comprises, before the deformation step and after the annealing step, a step of depositing on said billet a layer of ductile material selected from copper, nickel, copper-nickel alloys, copper-manganese alloys, gold, silver, nickel-phosphorus Ni-P and nickel-boron Ni-B to facilitate the wire forming operation. The thickness of the deposited layer of ductile material is preferably selected so that, for a given wire cross-sectional area, the ratio of the ductile material area to the NbHf alloy area is less than 1, preferably less than 0.5, more preferably between 0.01 and 0.4.

[0022] Such a manufacturing method facilitates the shaping of the NbHf alloy billet into a wire, and more particularly facilitates the drawing, wire drawing and rolling operations. In particular, this method is advantageous for manufacturing a balance spring having the following composition:

[0023] -Niobium: up to 100% by weight

[0024] - hafnium: between 5 and 15% by weight, preferably between 8 and 12% by weight,

[0025] - one or more elements selected from Ti, Zr, Ta and W, the percentage of each element being in the range of 0.2 to 1.5 wt. %,

[0026] - Impurities, the total percentage of which is in the range from 0 to 0.5% by weight. DETAILED DESCRIPTION

[0027] The invention relates to a method for manufacturing a balance spring to be fitted to a balance wheel of a timepiece movement and made of an alloy containing niobium and hafnium.

[0028] The method comprises the following steps:

[0029] - a step of manufacturing a billet made of a niobium and hafnium alloy, said alloy containing:

[0030] -Niobium: up to 100% by weight

[0031] - hafnium: between 5 and 60% by weight, preferably between 5 and 30% by weight, more preferably between 8 and 12% by weight,

[0032] - one or more elements selected from Ti, Zr, Ta and W, the percentage of each element being in the range of 0 to 2 wt. %, preferably in the range of 0.2 to 1.5 wt. %,

[0033] - impurities, the total percentage of which is in the range of 0 to 0.5 wt. %. More specifically, the impurities may be trace elements selected from O, H, C, Fe, N, Ni, Si, Cu, Al, Cr, Mn, V, Sn, Mg, Mo, Pb, Co and B, each of which is present in an amount of 0 to 1,000 wt. ppm,

[0034] - a step of annealing the billet followed by cooling the billet,

[0035] - a step of depositing ductile material on said blank,

[0036] - at least one step of deforming the blank to form a wire, with annealing and cooling steps between the deformation steps in the case of a plurality of deformation steps,

[0037] - a winding step for forming a balance spring,

[0038] - A final heat treatment step to fix the shape of the balance spring and adjust the thermoelastic coefficient.

[0039] In a particularly preferred manner, the blank contains 8 to 12 wt. % hafnium, Ti, Zr, Ta and W, the percentage of each element being in the range of 0.2 to 1.5 wt. %, more preferably Ti in the range of 0.5 to 1.5 wt. %, Zr in the range of 0.5 to 0.9 wt. %, Ta in the range of 0.3 to 0.7 wt. % and W in the range of 0.3 to 0.7 wt. %.

[0040] Preferably, the NbHf alloy billet used in the present invention does not contain any other elements except any potential and unavoidable trace elements. This can prevent the formation of brittle phases.

[0041] More particularly, the oxygen content is less than or equal to 0.10% by weight of the total composition, in particular less than or equal to 0.05% by weight of the total composition, or even less than or equal to 0.03% by weight of the total composition.

[0042] More particularly, the carbon content is less than or equal to 0.04% by weight of the total composition, in particular less than or equal to 0.02% by weight of the total composition, or even less than or equal to 0.015% by weight of the total composition.

[0043] More particularly, the iron content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.02% by weight of the total composition, or even less than or equal to 0.005% by weight of the total composition.

[0044] More particularly, the nitrogen content is less than or equal to 0.04% by weight of the total composition, in particular less than or equal to 0.02% by weight of the total composition, or even less than or equal to 0.015% by weight of the total composition.

[0045] More particularly, the hydrogen content is less than or equal to 0.01% by weight of the total composition, in particular less than or equal to 0.0035% by weight of the total composition, or even less than or equal to 0.001% by weight of the total composition.

[0046] More particularly, the silicon content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.02% by weight of the total composition, or even less than or equal to 0.005% by weight of the total composition.

[0047] More particularly, the nickel content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0048] More particularly, the content of the element in ductile solid solution, such as copper, in the alloy is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.004% by weight of the total composition.

[0049] More particularly, the aluminum content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0050] More particularly, the chromium content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0051] More particularly, the manganese content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0052] More particularly, the vanadium content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0053] More particularly, the tin content is less than or equal to 0.01% by weight of the total composition, in particular less than or equal to 0.0035% by weight of the total composition, or even less than or equal to 0.001% by weight of the total composition.

[0054] More particularly, the magnesium content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0055] More particularly, the molybdenum content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0056] More particularly, the lead content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0057] More particularly, the cobalt content is less than or equal to 0.01% by weight of the total composition, in particular less than or equal to 0.0035% by weight of the total composition, or even less than or equal to 0.001% by weight of the total composition.

[0058] More particularly, the boron content is less than or equal to 0.005% by weight of the total composition, in particular less than or equal to 0.0001% by weight of the total composition.

[0059] The annealing step is a solution treatment in vacuum at a temperature of 650°C to 1,750°C for preferably 5 minutes to 2 hours, followed by quenching in gas, for example, to obtain a supersaturated solid solution of Hf in β-phase Nb. According to another embodiment, natural cooling in vacuum is also conceivable.

[0060] More particularly, the deposition step for forming the object of the invention consists of depositing a layer of ductile material selected from copper, nickel, copper-nickel alloys, copper-manganese alloys, gold, silver, nickel-phosphorus Ni-P and nickel-boron Ni-B to facilitate the wire forming operation. Preferably, the thickness of the deposited ductile material layer is selected so that the ratio of the ductile material area to the NbHf alloy area at a given wire cross-sectional area is less than 1, preferably less than 0.5, more preferably in the range of 0.01 to 0.4. For example, for a total wire diameter of 0.1 mm, the ductile material layer may have a thickness of 7 μm at a cross-sectional area of ​​the NbHf alloy of 0.086 mm in diameter. This corresponds to a copper area of ​​0.35 (0.002 mm 2) and NbHf area (0.0058mm 2 ) ratio.

[0061] This thickness of ductile material, particularly copper, makes it easy to draw, wire draw and roll the composite Cu / NbHf material. More specifically, the copper thickness is optimized so that the tip created by filing or hot drawing required to insert the wire into the drawing plate during the drawing or wire drawing operation is coated with copper.

[0062] Ductile material, preferably copper, is therefore deposited at a given moment to facilitate the wire forming operations by drawing, wire drawing and rolling, retaining a thickness of preferably 1 to 500 microns on a wire having an overall diameter of 0.2 to 1 mm.

[0063] The addition of ductile material can be electroplated, by PVD or CVD or mechanical; in this case it is a sleeve or tube of ductile material such as copper conditioned on a large diameter NbHf alloy rod, which is then tapered during one or more deformation steps of the composite rod. Thus, one possibility involves forming a composite billet by assembling the Nb-Hf rod and the copper sleeve, which is then extruded.

[0064] The deformation step refers in general to one or more deformation treatments, which may include wire drawing and / or rolling. Wire drawing requires the use of one or more drawing plates in the same deformation step or in different deformation steps, if necessary. Wire drawing is performed until a wire with a circular cross section is obtained. Rolling may be performed during the same deformation step as wire drawing or in another subsequent deformation step. Advantageously, the final deformation treatment applied to the alloy is a rolling operation, preferably with a rectangular profile compatible with the inlet cross section of a winder spindle.

[0065] The method may include one or more deformation steps, each step having a deformation ratio in the range of 1 to 5, preferably in the range of 2 to 5, the deformation ratio satisfying the general formula 2ln(d0 / d), where d0 and d are the diameters before and after deformation, respectively. The total deformation ratio may be in the range of 1 to 14.

[0066] The method may comprise intermediate annealing steps between the different deformation steps.

[0067] The method of the invention preferably comprises, after the deformation step, a step of removing said layer of ductile material. Preferably, the ductile material is removed once all deformation operations have been carried out, i.e. after the final rolling operation and before the coiling operation. However, this does not exclude the removal of the layer of ductile material before all deformation operations have been completed. Thus, when rolling in multiple stages, the layer of ductile material may be removed before the final rolling stage. Preferably, the layer of ductile material, such as copper, is removed from the wire, in particular by etching with a cyanide-based or acid-based solution, such as nitric acid.

[0068] Except for the intermediate annealing operation performed between the deformation steps, the annealing before the deformation step is performed at a temperature of 650° C. to 1,750° C. for a duration of 5 minutes to 2 hours, preferably 10 minutes to 1 hour.

[0069] The final heat treatment after coiling is carried out at a temperature of 500 to 1,250° C. for a duration of 30 minutes to 30 hours. Depending on the composition and temperature of the alloy, a body-centered cubic single-phase structure or a two-phase structure having a body-centered cubic structure and a hexagonal close-packed structure can be obtained at the end of this heat treatment.

[0070] The method of the invention makes it possible to manufacture, and more particularly to shape, a balance spring made of an alloy of the niobium-hafnium type. This alloy has high mechanical properties, combining a very high yield strength, greater than 600 MPa, with a very low elastic modulus, of the order of 60 GPa to 100 GPa. This combination of properties is very suitable for a balance spring. Moreover, this alloy is paramagnetic.

[0071] Binary alloys containing niobium and hafnium of the type described above and used in the implementation of the invention also have an effect similar to that of "Elinvar", having a thermoelastic coefficient of almost zero within the normal operating temperature range of a watch and are suitable for making self-compensating balance springs.

Claims

1. A method for manufacturing a hairspring to be assembled on a balance wheel of a timepiece movement, comprising: - a step of manufacturing a billet made of a niobium and hafnium alloy, said alloy containing: -Niobium: up to 100% by weight -Hafnium: between 5 and 60% by weight, - one or more elements selected from Ti, Zr, Ta and W, the percentage of each element being in the range of 0 to 2 wt. %, - impurities, the total percentage of which is in the range of 0 to 0.5% by weight, - a step of annealing and cooling said billet, - at least one step of deforming the annealed billet to form a wire, - a winding step for forming a balance spring, - Final step of heat treatment of the balance spring, It is characterized in that it comprises, before the deformation step, a step of depositing on the billet a layer of ductile material selected from copper, nickel, copper-nickel alloy, copper-manganese alloy, gold, silver, nickel-phosphorus Ni-P and nickel-boron Ni-B to facilitate the wire forming operation.

2. The method according to claim 1, characterized in that The alloy contains between 5 and 30 wt. % hafnium.

3. The method according to claim 1, characterized in that The alloy contains between 8 and 12 weight percent hafnium.

4. The method according to claim 1, characterized in that The alloy contains one or more elements selected from Ti, Zr, Ta and W, and the percentage of each element is in the range of 0.2 to 1.5 wt%.

5. The method according to claim 1, characterized in that The thickness of the deposited ductile material layer is selected so that the ratio of ductile material area to alloy area is less than 1 for a given wire cross-sectional area.

6. The method according to claim 1, characterized in that The thickness of the deposited ductile material layer is selected so that the ratio of ductile material area to alloy area is less than 0.5 for a given wire cross-sectional area.

7. The method according to claim 1, characterized in that The thickness of the deposited ductile material layer is selected so that the ratio of ductile material area to alloy area is in the range of 0.01 to 0.4 for a given wire cross-sectional area.

8. A method according to any one of claims 1 to 7, characterised in that It comprises, before the winding step, the step of removing the layer of ductile material.

9. A method according to any one of claims 1 to 7, characterised in that The deformation step is performed by wire drawing and / or rolling.

10. The method according to claim 8, characterized in that The deformation step is performed by wire drawing and / or rolling.

11. A method according to any one of claims 1 to 7, characterised in that It comprises one or more deformation steps, wherein for each step deformation is performed at a deformation rate in the range of 1 to 5, the total accumulation of deformations over all steps resulting in a total deformation rate in the range of 1 to 14.

12. The method according to claim 10, characterized in that It comprises one or more deformation steps, wherein for each step deformation is performed at a deformation rate in the range of 1 to 5, the total accumulation of deformations over all steps resulting in a total deformation rate in the range of 1 to 14.

13. A method according to any one of claims 1 to 7, characterised in that It includes annealing and cooling steps between the deformation steps.

14. The method according to claim 12, characterized in that It includes annealing and cooling steps between the deformation steps.

15. A method according to any one of claims 1 to 7, characterised in that Each annealing and cooling step is a solution treatment at a temperature of 650° C. to 1,750° C. in vacuum for 5 minutes to 2 hours, followed by quenching in gas or natural cooling in vacuum to obtain a supersaturated solid solution of Hf in Nb.

16. The method according to claim 14, characterized in that Each annealing and cooling step is a solution treatment at a temperature of 650° C. to 1,750° C. in vacuum for 5 minutes to 2 hours, followed by quenching in gas or natural cooling in vacuum to obtain a supersaturated solid solution of Hf in Nb.

17. A method according to any one of claims 1 to 7, characterised in that The final heat treatment step is performed at a temperature of 500° C. to 1,250° C. for a duration of 30 minutes to 30 hours.

18. The method according to claim 16, characterized in that The final heat treatment step is performed at a temperature of 500° C. to 1,250° C. for a duration of 30 minutes to 30 hours.

Citation Information

Patent Citations

  • Lightweight precious alloy made from titanium and gold, and timepiece or jewellery item component made from a lightweight precious alloy of titanium and gold

    CN106460094A

  • Automatic compensation balance spring for balance spring / balance wheel vibrator of clock movement and method for making same

    CN1206861A

  • Self compensation coil spring of oscillator of watch movement, and method for treating same

    CN1268682A

  • Self-compensating spring for clockwork movement spring balance and method for treating the same

    EP1039352A1

  • Self-compensating spiral spring for a mechanical balance-spiral spring oscillator

    US20020180130A1